The effects of ozone therapy on extremity ischemia-reperfusion injury in a rabbit model - Ganime Coban; Burak Kaymaz; Umut Hatay Golge; Ferdi Goksel; Erkam Komurcu; Huseyin Toman (SERNEV, 2019)
Introduction: Ischemia is reversible orirreversible cell/tissue damage that is secondary to insufficient blood flow totissues or organs. Ischemia causes many metabolic and structural changes at thecellular level. Ozone therapy is often used as an antioxidant remedy. Thisstudy aimed to investigate the effects of ozone therapy on extremityischemia-reperfusion (IR) injury.Methods: Twenty-four New ZealandWhite (NZW) rabbits were randomly allocated into three groups. Each groupconsisted of eight rabbits. Group I was the control group, Group II was theischemia group, and Group III, the ozone group.Femoral arteries of the right legs were dissected, and femoral arterialocclusion was performed in Group II and III.Hematological and histopathological evaluation was performed in allgroups.Results: The levels of totalantioxidant status (TAS) after the surgical procedure was higher in the ozonegroup compared to the ischemia group (p=0.036). In addition, the levels ofmalondialdehyde (MDA) after the surgical procedure were lower in the ozonegroup compared to the ischemia group but not statistically significant(p=0.093). The control and ozone groups were histopathologically similar.Conclusions: Ozone therapy may be usedas an alternative treatment modality with its anti-inflammatory and antioxidanteffects for the treatment of extremity IR injury.